Moving Paperwork: Political Communication and the Making of Archives in the Spanish Empire - Cunill, Caroline (2022)
This article aims at identifying some of the actors responsible for the transportation of records from America to the Iberian Peninsula in the sixteenth century. We will also show how their intervention had an impact on political communication in the Spanish empire. Our goal is to analyse the formation of archives from the perspective of the agents who were charged with their transportation. We will examine the role that Indigenous messengers, as well as the lawyers who were expected to represent the Spanish King’s vassals from the overseas territories before the Council of the Indies in Spain played in the circulation, use and conservation of the records in the empire. Since it is impossible to be exhaustive, the analysis will be built on a series of examples relative to the province of Yucatán in New Spain.